Organic vapor sensing behaviors of 4D printed thermoplastic polyamide elastomer by selective laser sintering - Shuxiang Mei; Zhen Li; Xiaoyin Chen; Wei Zhao; Yuancheng Zhang; Xiaomeng Zhang; Zhe Cui; Peng Fu; Xinchang Pang; Minying Liu (Journal of Materials Research and Technology, 2023)
Thermoplastic polyamide elastomer (TPAE) films were prepared by selective laser sintering technology and their organic vapor sensing behaviors were investigated. The stable responsive electrical signal was attributed to the conductive pathways evolution formed by polyetheramine soft segments. And the response behaviors of the TPAE films were evaluated using organic vapors of different polarities. Unlike conventional materials that only respond to some specific organic vapors, TPAE showed a high negative vapor coefficient (NVC) effect for all tested vapors. Rapid response, high responsivity and good repeatability were observed in continuous immersion drying run (IDR) experiments at 20 °C. The sensing behaviors during the breathing tests showed a good discrimination for different ethanol vapor concentrations. This study not only provides a guidance for the preparation of organic vapor sensors with fast response, high responsivity and stable repeatability, but also provides a strategy to broaden the application of TPAE into 4D printing field.